Intermolecular Multiple Dehydrogenative Cross‐Couplings of Ketones with Boronic Acids and Amines via Copper Catalysis. Issue 16 (12th July 2019) - Wang, Tianzhang; Chen, Guowei; Lu, Yu‐Jing; Chen, Qian; Huo, Yanping; Li, Xianwei
Abstract: An efficient and versatile oxidative coupling reaction was developed for the synthesis of valuable β‐functionalized unsaturated ketones and meta ‐substituted phenols. In the case of intramolecular reactions, achieving rapid molecular complexity through multiple dehydrogenative couplings is already a well‐established strategy. Herein, we report an intermolecular multiple dehydrogenative coupling between ketones and nucleophilic amines or boronic acids using inexpensive copper(I) oxide as a catalyst. This method provides a facile access to highly desirable chemical products such as α, β‐unsaturated ketones, enaminones, and synthetically relevant meta ‐substituted phenols. Abstract :